Evaluating social interaction performance and sense of community in urban green space: the case of Trabzon Ganita coast - Özkan, Doruk Görkem; Özkan, Sinem Dedeoğlu (Landscape Architecture and Art, 2024)
As population increases in urban centers, urban open spaces are gradually diminishing and the quality of existing spaces is deteriorating. Therefore, when designing open spaces in cities facing issues such as population growth, unplanned urbanization, industrialization, and transportation problems, social dimensions should be considered as much as ecological and economic dimensions. This study focuses on the Ganita Coastal Project, one of the identity spaces of the city of Trabzon. The aim is to determine the social performance of urban open space organizations formed after the implementation of the project and to reveal their effects on the sense of community. The research method consists of surveys that include the evaluation of the social interaction performance provided by the place and the assessment of the sense of community. The research results show that the social interaction performance of the place has a positive and significant relationship with the sense of community. This study defines the sub-dimensions of social features by focusing solely on the social characteristics of the place. The social factors affecting the sense of community are identified as the functional, social, and perceptual sub-dimensions, respectively. The success of the social features such as popularity of place, social accessibility, and variety of activities has allowed for the intense use of this space. This research focuses on the social interaction performance but cannot claim to have examined all the features of the place that constitute social interaction. Considering the importance of urban open spaces as a social stage and their significance in forming relationships between people and places as well as among people themselves, the findings of this study are quite important. The results, especially regarding which social features of a place should be taken into account when designing new urban spaces, can be guiding for both designers and managers.